Upaya Kepala Madrasah dalam Meningkatkan Profesionalisme Guru - Mulajimatul Fitria; Slamet Slamet (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explore efforts to improve teacher professionalism and determine the supporting and inhibiting factors of the madrasah principal's efforts at MTS Arrabi Tamansuruh. Using a qualitative descriptive approach, data collection methods include observation, interviews, and documentation. Data were analyzed using an interactive analysis model. The results of the study indicate that the madrasah principal plays an important role in improving the personality and skills of teachers through role models. In addition, increasing capacity through training, implementing teacher working group (KKG) programs to providing facilities and resources. The madrasah principal also focuses on motivating and rewarding teachers. In addition, several supporting factors are also listed, including managerial support, availability of resources, teacher motivation, partnerships and collaboration. While inhibiting factors include lack of support from human resources in accordance with the field of science, lack of awareness, teacher commitment, changes in curriculum and policies and budget constraints that prevent teachers from participating in training and self-development.